Unraveling the Health Effects of Environmental Mixtures: An NIEHS Priority - Carlin, Danielle J.; Rider, Cynthia V.; Woychik, Rick; Birnbaum, Linda S. (Environmental health perspectives, 2013)
[...]unbiased approaches (i.e., approaches that provide comprehensive characterization of exposure without an a priori hypothesis) such as the exposome are needed to move beyond "looking under the lamppost" (i.e., only measuring exposure for chemicals with available toxicology data). [...]participants in the NIEHS Mixtures Workshop discussed the importance of developing mixtures-related databases. Because it is challenging to search the literature for interactions among chemicals, there was a great deal of interest in the development of databases that would accommodate different levels of mixture study results (i.e., in vitro studies to human studies).